The Role of Interactive Education in Improving Emotional Relationships between Children and Parents at Bakti Sawahan Kindergarten - Habibah, Cendani Lulu; Wijayanti, Wijayanti (Jurnal Empathy Pengabdian Kepada Masyarakat, 2025)
Background: Children aged 0-6 years undergo rapid development crucial for their future, with parents serving as primary educators shaping their behavior and emotions. Parental involvement in education fosters social-emotional development, including emotion management and relationship building. Educating children and parents on prevention through innovative strategies, the Tree of Life is essential to address this. This activity aims to increase awareness and knowledge about violence prevention and strengthen parental roles in supporting children’s social-emotional development. Methods: The study involved 33 large-class students and 18 parents, using educational modules, questionnaires, and tools like Tree of Life and Aircraft Quiz. The implementation method includes the preparation of modules, outreach to children and parents, the use of interactive media such as the Tree of Life and Aircraft Quiz, as well as pretest-post test evaluation. Results: The Tree of Life, resembling an artificial plant with colorful leaves, effectively illustrated life and positive behavior. The community service program at Bakti Sawahan Islamic Kindergarten significantly improved children's understanding of violence, with pretest scores of 95.6% and posttest scores of 98.3%. Parents' awareness of their role in preventing violence increased from 77.2% to 91.0%. Conclusion: The education program significantly improved knowledge of social-emotional violence among both children and parents. The program is recommended to continue and be integrated into the curriculum to enhance children's social-emotional development and ensure a safe environment. ers social-emotional development, including emotion management and relationship building. Educating children and parents on prevention through innovative strategies, the Tree of Life is essential to address this. This activity aims to increase awareness and knowledge about violence prevention and strengthen parental roles in supporting children’s social-emotional development.  Methods: The study involved 33 large-class students and 18 parents, using educational modules, questionnaires, and tools like Tree of Life and Aircraft Quiz. The implementation method includes the preparation of modules, outreach to children and parents, the use of interactive media such as the Tree of Life and Aircraft Quiz, as well as pretest-post test evaluation.  Results: The Tree of Life, resembling an artificial plant with colorful leaves, effectively illustrated life and positive behavior. The community service program at Bakti Sawahan Islamic Kindergarten significantly improved children's understanding of violence, with pretest scores of 95.6% and posttest scores of 98.3%. Parents' awareness of their role in preventing violence increased from 77.2% to 91.0%.  Conclusion: The education program significantly improved knowledge of social-emotional violence among both children and parents. The program is recommended to continue and be integrated into the curriculum to enhance children's social-emotional development and ensure a safe environment.